Analisis Minat Konsumen Terhadap Produk Tempe Di Pasar Tanjong Mesjid Kecamatan Samudera Kabupaten Aceh Utara - Koko Junaidi (Universitas Medan Area, 2026)
This research was conducted at Tanjong Mesjid Market in Samudera District, which is a place for processing agricultural products that has a significant role in improving the national economy. Tempeh is one of the traditional foods in Indonesia and is the largest producer country in the world. Tempeh sales at Tanjong Mesjid Market, Samudera District, show a difference in sales between tempeh branded with the rose flower brand and tempeh branded with the Aceh rose flower brand. This study aims to analyze consumer interest in tempeh products at Tanjung Mesjid Market, Samudera District, by determining which attributes are most dominantly considered by consumers in making purchasing decisions between tempeh branded with the rose flower brand and the Aceh rose brand. The research method used is a quantitative descriptive approach by processing data using the conjoint analysis method. The results of the study showed that the order of attributes most considered by consumers in purchasing decisions between tempe cap bunga mawar and mawar aceh at Tanjung Mesjid Market, Samudera District was in terms of size with an NPR value of (41.144), price with an NPR value of (30.144), brand with an NPR value of (21.589) and shape with an NPR value of (6.522). Overall, the combination of attributes that became consumers' interest was the brand of tempe cap bunga mawar, the square shape, small size and the price of Rp. 2,000.